2012
DOI: 10.1017/s0047279412000736
|View full text |Cite
|
Sign up to set email alerts
|

Civility, Community Cohesion and Antisocial Behaviour: Policy and Social Harmony

Abstract: Intergroup conflict, whether manifest as the absence of community cohesion or as the presence of antisocial behaviour, is an issue of international concern. In the UK, confronting the reality or perceived threat of intergroup conflict is a core feature of community cohesion and antisocial behaviour policies. To varying degrees, the frameworks underpinning these policies see the absence or breakdown of community relations as a cause of social disharmony. A key challenge for policy is therefore improvement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…Older people living in areas perceived to have high crime, in particular antisocial behaviour, may be less likely to enjoy personal security, less able to leave their homes, and consequently have fewer opportunities for interaction (Wigfield and Alden, 2015;. Bannister and O'Sullivan (2013) reached similar conclusions about the damaging role of anti-social behaviour in relation to social cohesion, rendering people afraid to go out or visit certain places. Research findings from Sweden suggest that the cause of fear and insecurity among older people arises not only from the threat of violence and crime but also from other factors such as disease and health care crises, dependency on others, and the loss of significant others (Jakobson and Hallberg, 2005).…”
Section: Domain Three: Personal Securitymentioning
confidence: 99%
“…Older people living in areas perceived to have high crime, in particular antisocial behaviour, may be less likely to enjoy personal security, less able to leave their homes, and consequently have fewer opportunities for interaction (Wigfield and Alden, 2015;. Bannister and O'Sullivan (2013) reached similar conclusions about the damaging role of anti-social behaviour in relation to social cohesion, rendering people afraid to go out or visit certain places. Research findings from Sweden suggest that the cause of fear and insecurity among older people arises not only from the threat of violence and crime but also from other factors such as disease and health care crises, dependency on others, and the loss of significant others (Jakobson and Hallberg, 2005).…”
Section: Domain Three: Personal Securitymentioning
confidence: 99%
“…By examining the far-reaching capabilities of PSPOs, this article has suggested that these developments have created a tool whereby local councils have the potential to exclude and criminalise vulnerable groups from public spaces; based on decreasing tolerance levels towards difference and hardening perceptions of deservedness. We have demonstrated how Bannister and O'Sullivan's (2013) conceptions of civility and ASB policy have evolved following the introduction of the new legislation, by suggesting how civility is now increasingly conceptualised and enforced at a local level, without scrutiny.…”
Section: Resultsmentioning
confidence: 99%
“…In Australia and elsewhere, programs and policies addressing cultural diversity have traditionally been designed for community‐scale implementation, and often have been set up to encourage interactions within and across neighbourhoods (Bannister & O'Sullivan, ). Some other programs and policies facilitate cross‐cultural exchanges across institutions such as schools, local clubs, and religious associations (Department of Communities and Local Government, ).…”
Section: Growing Global Diversity and Densitymentioning
confidence: 99%